Memory T cell–mediated rejection is mitigated by FcγRIIB expression on CD8+ T cells. Issue 8 (24th March 2020) - Morris, Anna B.; Pinelli, David F.; Liu, Danya; Wagener, Maylene; Ford, Mandy L.
Abstract : Donor‐reactive memory T cells generated via heterologous immunity represent a potent barrier to long‐term graft survival following transplantation because of their increased precursor frequency, rapid effector function, altered trafficking patterns, and reduced reliance on costimulation signals for activation. Thus, the identification of pathways that control memory T cell survival and secondary recall potential may provide new opportunities for therapeutic intervention. Here, we discovered that donor‐specific effector/memory CD8 + T cell populations generated via exposure to acute vs latent vs chronic infections contain differential frequencies of CD8 + T cells expressing the inhibitory Fc receptor FcγRIIB. Results indicated that frequencies of FcγRIIB‐expressing CD8 + donor‐reactive memory T cells inversely correlated with allograft rejection. Furthermore, adoptive T cell transfer of Fcgr2b −/− CD8 + T cells resulted in an accumulation of donor‐specific CD8 + memory T cells and enhanced recall responses, indicating that FcγRIIB functions intrinsically to limit T cell CD8 + survival in vivo. Lastly, we show that deletion of FcγRIIB on donor‐specific CD8 + memory T cells precipitated costimulation blockade‐resistant rejection. These data therefore identify a novel cell‐intrinsic inhibitory pathway that functions to limit the risk of memory T cell–mediated rejection following transplantation and suggest that therapeutic manipulation of this pathway could improve outcomes in sensitized patients. Abstract : Signaling through the inhibitory FcγRIIB receptor regulates graft‐specific CD8 + memory T cell immunity in a cell‐autonomous manner. See the editorial from Cravedi on page 1967 .